2023
DOI: 10.2147/ijn.s385395
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-133a-3p Derived from BMSCs Alleviates Cerebral Ischemia-Reperfusion Injury via Targeting DAPK2

Abstract: Background: Cerebral ischemia-reperfusion (CI/R) injury is a subtype of complication after treatment of ischemic stroke. It has been reported that exosomes derived from BMSCs could play an important role in CI/R injury. However, whether BMSCs-derived exosomes could regulate CI/R injury via carrying miRNAs remains to be further explored. Methods: RNA sequencing was performed to identify the differentially expressed miRNAs. To mimic CI/R in vitro, SH-SY5Y cells were exposed to oxygen glucose deprivation/reoxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Based on the ability to cross the vessel barrier, excellent biocompatibility, and low immunogenicity, exosomes have emerged as efficient nanoscale messengers for cells or cell-tissue communications [ 16 , 29 ]. Mounting evidence suggests that exosomes possess great capacity to deliver protective non-coding RNAs [ 30 , 31 ], miRNAs [ 32 , 33 ], and healthy organelles [ 34 ] for the treatment of ischemic diseases. ASCs are abundant in source, easy to be harvested and modified, and can robustly release exosomes, which would meet huge clinical demands in future [ 18 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ability to cross the vessel barrier, excellent biocompatibility, and low immunogenicity, exosomes have emerged as efficient nanoscale messengers for cells or cell-tissue communications [ 16 , 29 ]. Mounting evidence suggests that exosomes possess great capacity to deliver protective non-coding RNAs [ 30 , 31 ], miRNAs [ 32 , 33 ], and healthy organelles [ 34 ] for the treatment of ischemic diseases. ASCs are abundant in source, easy to be harvested and modified, and can robustly release exosomes, which would meet huge clinical demands in future [ 18 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stromal cell-derived exosomes have protective effects against CIRI (13). Moreover, some molecules from BMSC-derived exosomes such as miR-133a-3p (32), long noncoding RNA KLF transcription factor 3 antisense RNA 1 (lncRNA KLF3-AS1) (33), and KLF transcription factor 4 (KLF4) (34) also improved CIRI. Our data showed that BMSC-derived exosomal NRF2 promoted the mRNA and protein expression of Lin28a.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, elucidating the roles of all cargoes in EVs is challenging, and most researchers only pay close attention to the cargoes of interest, ignoring other potentially valuable content. Differential miRNA expression in tissues, cells, serum, plasma, and other samples has been detected by miRNA sequencing or microarray chip technology, and a single miRNA has been selected for subsequent research [ 201 204 ]. However, the mechanisms of other miRNAs and the synergistic mechanisms of multiple miRNAs have not been revealed.…”
Section: Challenges and Prospectsmentioning
confidence: 99%